(untitled) (Global Journal of Human-Social Science, 2018)
This qualitative study aims to investigate whether the use of the notional syllabus in an Intercultural Communication (IC) Course in Sweden satisfies Chinese exchange students’ needs, and to evaluate to what extent their needs are met. The research approach adopted in this article includes a structured interview and introspection. The findings indicate that with the aid of the notional syllabus, the course meets Chinese learners’ demands on the aspects of situation, stakeholder and theory. It should also be highlighted that lacking systemic language instructions is an inherent weakness of the notional syllabus. How to balance the requirements of both the IC and English for Specific Purpose (ESP) course to fulfill learners’ needs is mainly determined by the teacher.